2014
DOI: 10.4103/2249-4863.148127
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of overweight/obesity among adolescents in an Urban City of North India

Abstract: Background and objectives:Obesity and overweight is a growing pandemic affecting millions of adolescents in developed as well as developing countries. Obesity is associated with the onset of major chronic diseases leading to complications and also psychosocial problems in adolescents. The greater concern is that the risks of obesity during childhood will persist into adolescence and adulthood. The objectives of the study were to assess the prevalence of being overweight and obesity and to study the associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 17 publications
3
23
0
Order By: Relevance
“…Obesity is not only an important preventable cause of death but is also the most neglected one throughout the world. 1,17 Thus surveillance programs for identifying population groups at higher risk of developing obesity and related complications can optimize the use of scarcely available health resources.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is not only an important preventable cause of death but is also the most neglected one throughout the world. 1,17 Thus surveillance programs for identifying population groups at higher risk of developing obesity and related complications can optimize the use of scarcely available health resources.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of overweight and obesity have escalated rapidly among Indian adolescents (20) who typified typical college going students transitioning from adolescence to young adulthood. Indians, as an ethnic group, are particularly at high risk for MS and central obesity, both forerunners of diabetes, CHD and other "life style" disorders (7,8,21).Overweight and obesity significantly contribute to the development of MS among college students (13,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…In India, a study involving 1900 children aged 10–19 years in 2014 showed the prevalence of overweight and obesity to be 11.0 and 5.7%, respectively. The authors argued that facility transport and fast/junk foods were the leading factors for the results …”
Section: Discussionmentioning
confidence: 99%
“…The authors argued that facility transport and fast/junk foods were the leading factors for the results. 39 In 2015, a study in Shanghai, China, analysed factors related to lifestyle and high weight in 2400 children aged 6-11 years. The prevalence of obesity and overweight together was 26.8%.…”
Section: Figurementioning
confidence: 99%